A Broad Continuous Temperature Tunable DBR Single-Frequency Fiber Laser at 1064 nm - Yuning Zhang; Can Li; Shanhui Xu; Huaqiu Deng; Zhouming Feng; Changsheng Yang; Xiang Huang; Yuanfei Zhang; Jiulin Gan; Zhongmin Yang (IEEE Photonics Journal, 2016)
Based on a temperature-dependent longitudinal-mode-selection model, a broad temperature range for single-longitudinal-mode (SLM) operation of a short DBR phosphate fiber laser has been demonstrated. In order to make the variety in cavity resonance wavelength match the reflection peak changing in fiber Bragg grating (FBG) when the ambient temperature changes, the packaging materials with different coefficient of linear expansion are used for the active fiber and the FBG, respectively. The temperature variation range without mode hopping of the SLM fiber laser has been increased from about 2 °C to over 20 °C, while the continuous tunable wavelength range broadened to be > 149 pm.